Safety and feasibility of an enhanced recovery pathway after a liver resection: prospective cohort study. Issue 8 (August 2015) - Dasari, Bobby V.M.; Rahman, Rasha; Khan, Shakeeb; Bennett, Davinia; Hodson, James; Isaac, John; Marudanayagam, Ravi; Mirza, Darius F.; Muiesan, Paolo; Roberts, Keith J.; Sutcliffe, Robert P.
Abstract: Background: In contrast to colorectal surgery, enhanced recovery pathways (ERPs) have not yet become standard practice after major upper abdominal surgery. The aim of this study was to assess the feasibility and outcomes after implementation of an ERP after liver a resection. Methods: Patients who underwent a liver resection in two consecutive 6-month periods before (July–December 2013) and after (January–June 2014) implementation of an ERP were included in a prospective study. Patients who underwent live donation, ALPPS (associating liver partition with portal vein ligation for staged hepatectomy) or concomitant procedures were excluded. Peri-operative outcomes were compared between groups, and multivariate analysis of factors influencing the length of hospital stay (LOS) was performed. Results: Two hundred and eleven patients (93 pre-ERP and 91 post-ERP patients) underwent a liver resection during the study period. There was no significant difference in the median LOS ( P  = 0.907) and 30-day readmission rates ( P  = 0.645) between the groups. Severe (Clavien grade III–V) complications were reduced in ERP patients (13.9% versus 4.3%; P  = 0.039). On multivariate analysis, an increased age (< 0.001), open resection (< 0.001) and complications (< 0.001) were associated with an increased LOS. Conclusion: Enhanced recovery after a liver resection appears to be safe, feasible and may reduce severe complications. However, the LOS was significantly influenced by patient age, open surgery and post-operative complications, but not by an ERP.